A novel diarylheptanoid-bearing sesquiterpene moiety from the rhizomes of Alpinia officinarum. Issue 20 (17th October 2016) - Wei, Na; Zhou, Zhonglin; Wei, Qing; Wang, Yong; Jiang, Jun; Zhang, Junqing; Wu, Lixiang; Dai, Shuiping; Li, Youbin
Abstract: A new diarylheptanoid analogue-bearing sesquiterpene moiety, named Alpinisin A, was isolated from the rhizomes of Alpinia officinarum Hance. The new structure was determined by various spectroscopic techniques 1 H-nuclear magnetic resonance ( 1 H NMR), 13 C-attached proton test ( 13 C-APT), heteronuclear single quantum coherence (HSQC), heteronuclear multiple bond correlation (HMBC), 1 H- 1 H correlation spectroscopy ( 1 H– 1 HCOSY), nuclear overhauser effect spectroscopy (NOESY) and high resolution electrospray ionization mass spectrometry (HR–ESI–MS). The compound was tested for cytotoxic activity in vitro against human tumour cell lines (gastric carcinoma cell -7901 (SGC-7901), Michigan Cancer Foundation-7 (MCF-7) and Caski), which showed significant inhibitory effects with IC50 levels of 11.42, 15.14 and 14.78 μM, respectively. The novel chemical structure characterised with a diarylheptanoid linked to a chain-like sesquiterpenoid should be highlighted. Abstract :